INTEGRITAS KEPEMIMPINAN TRANSFORMASIONAL SEBAGAI BEKAL SDM MENGHADAPI DOKTRIN PERTAHANAN INDONESIA DI ERA GEOPOLITIK BARU - Bambang Suyono; Andri Andriyanto Wibowo; Tarsisius Susilo; Muhammad Asep Apandi; Sahatro Silaban (Berajah Journal, 2025)
Global geopolitical shifts demand that Indonesia’s defense relies not only on technology but also on defense human resources with integrity. This study examines the role of integrity in transformational leadership as a strategic foundation for developing defense human resources in facing the defense doctrine within the new geopolitical era. A literature review with thematic analysis of scholarly articles, books, and policy documents was conducted. The findings show that integrity serves as a normative foundation that strengthens value consistency, leadership legitimacy, and preparedness against multidimensional threats. Honesty, consistency, moral courage, accountability, and empathy enhance professionalism, organizational cohesion, and adaptability. The discussion emphasizes that integrity-based transformational leadership not only reinforces defense doctrine but also elevates Indonesia’s global credibility. The study concludes that integrity-driven transformational leadership is a strategic asset for achieving the vision of Golden Indonesia 2045, while suggesting further empirical research for practical validation.